The Utility of Novel Urinary Biomarkers in Mice for Drug Development Studies. (January 2021) - Adedeji, Adeyemi O.; Gu, Yi-Zhong; Pourmohamad, Tony; Kanerva, Justin; Chen, Yafei; Atabakhsh, Elnaz; Tackett, Michael R.; Chen, Feifei; Bhatt, Bhavana; Gury, Thierry; Dorchies, Olivier; Sonee, Manisha; et al.
Novel urinary protein biomarkers have recently been identified and qualified in rats for the early detection of renal injury in drug development studies. However, there are few reports on the utility of these renal biomarkers in mice, another important and widely used preclinical animal species for drug development studies. The purpose of this study was to assess the value of these recently qualified biomarkers for the early detection of drug-induced kidney injury (DIKI) in different strains of mice using multiple assay panels. To this end, we evaluated biomarker response to kidney injury induced by several nephrotoxic agents including amphotericin B, compound X, and compound Y. Several of the biomarkers were shown to be sensitive to DIKI in mice. When measured, urinary albumin and neutrophil gelatinase-associated lipocalin were highly sensitive to renal tubular injury, regardless of the assay platforms, mouse strain, and nephrotoxic agents. Depending on the type of renal tubular injury, kidney injury molecule-1 was also highly sensitive, regardless of the assay platforms and mouse strain. Osteopontin and cystatin C were modestly to highly sensitive to renal tubular injury, but the assay type and/or the mouse strain should be considered before using these biomarkers. Calbindin D28 was highly sensitive to injury to the distal nephron in mice. To our knowledge, this is the first report that demonstrates the utility of novel urinary biomarkers evaluated across multiple assay platforms and nephrotoxicants in different mice strains with DIKI. These results will help drug developers make informed decisions when selecting urinary biomarkers for monitoring DIKI in mice for toxicology studies.